Cationic Polymers in Regenerative Medicine 2014
DOI: 10.1039/9781782620105-00001
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Cationic Polymers for Drug Delivery Applications

Abstract: Cationic polymers have attracted tremendous attention in recent years as non-viral vectors in gene delivery, owing to their high cellular uptake efficiency, good water solubility, excellent transfection efficiencies and facile synthesis. These polymers also show great potential for drug delivery applications, as their structure can be easily tailored to meet our growing understanding of the biological processes that govern biodistribution and biocompatibility of the carrier molecules. The incorporation of pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 139 publications
0
25
0
Order By: Relevance
“…Polyethyleneimine (PEI) is a polymer containing amine groups and aliphatic carbons that can be linear or branched. This polymer is used in detergents, adhesives, cosmetics, water treatment agents, and in CO 2 ‐capture applications . In particular, linear polyethyleneimine (Figure b) consists of a number of secondary amines and is insoluble in water, making it a great candidate for use as a basic heterogeneous buffer for the MOF‐catalyzed hydrolysis of nerve agents and simulants.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Polyethyleneimine (PEI) is a polymer containing amine groups and aliphatic carbons that can be linear or branched. This polymer is used in detergents, adhesives, cosmetics, water treatment agents, and in CO 2 ‐capture applications . In particular, linear polyethyleneimine (Figure b) consists of a number of secondary amines and is insoluble in water, making it a great candidate for use as a basic heterogeneous buffer for the MOF‐catalyzed hydrolysis of nerve agents and simulants.…”
Section: Figurementioning
confidence: 99%
“…This polymer is used in detergents, adhesives, cosmetics, water treatment agents, and in CO 2 -capture applications. [14] In particular,l inear polyethyleneimine ( Figure 1b)c onsists of an umber of secondary amines and is insoluble in water,m aking it ag reat candidate for use as ab asic heterogeneous buffer for the MOF-catalyzed hydrolysis of nerve agents and simulants. In this study,w ed emonstrate the hydrolysis of the simulant (DMNP) and nerve agents (GD and VX) with aM OF catalyst/ heterogeneous bufferm ixture.…”
mentioning
confidence: 99%
“…Also when useing the oligoamines and disulfide-containing cystamine bisacrylamide in the polyaddition the reducible disulfide bonds are introduce into the backbone of linear PAMAM. This method increases the biocompatibility of the polymer [121][122][123]. PAMAMs with amine or acrylamide terminal groups can be obtained by polyaddition from difunctional macromers.…”
Section: Step-growth Polymerizations In Synthesis Of Functional (Bio)mentioning
confidence: 99%
“…For example, the release of doxorubicin from Pluronic micelles could be achieved by insonation with low frequency ultrasound as reported by Husseini et al 30 or Marin et al 31 Like other cationic polymers, PDMAEMA is reported to be slightly cytotoxic and changes regarding the molecular architecture (for example copolymers with hydrophobic or hydrophilic monomers, branched system, chain ends) as well as the overall molar mass can significantly influence the cytotoxicity. [32][33][34][35] Moreover, it is reported that the masking effects of PDMAEMA complexes play a crucial role in the cytotoxicity. 34 To the best of our knowledge, the use of PDMAEMA as a multi-stimuli responsive polymer (and BCP thereof ) has not been reported for the selective release of photodynamic therapy (PDT) photosensitizers.…”
Section: Introductionmentioning
confidence: 99%